2016
DOI: 10.1128/aem.04071-15
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glycoside Hydrolase Family 113 Endo-β-1,4-Mannanase from Alicyclobacillus sp. Strain A4 and Insight into the Substrate Recognition and Catalytic Mechanism of This Family

Abstract: c Few members of glycoside hydrolase (GH) family 113 have been characterized, and information on substrate recognition by and the catalytic mechanism of this family is extremely limited. In the present study, a novel endo-␤-1,4-mannanase of GH 113, Man113A, was identified in thermoacidophilic Alicyclobacillus sp. strain A4 and found to exhibit both hydrolytic and transglycosylation activities. The enzyme had a broad substrate spectrum, showed higher activities on glucomannan than on galactomannan, and released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
4
18
0
2
Order By: Relevance
“…The catalytic residues are Glu-143 and Glu-223 in AxMan113A, as confirmed by site-directed mutagenesis and structural alignment to AaManA. Previous studies have shown that GH family 113 members hydrolyze mannooligosaccharides with DP Ͼ 3 and exhibit considerable transglycosylation activity (10,19). However, the smallest substrate of AxMan113A was M2 (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The catalytic residues are Glu-143 and Glu-223 in AxMan113A, as confirmed by site-directed mutagenesis and structural alignment to AaManA. Previous studies have shown that GH family 113 members hydrolyze mannooligosaccharides with DP Ͼ 3 and exhibit considerable transglycosylation activity (10,19). However, the smallest substrate of AxMan113A was M2 (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…The specific activity of AxMan113A toward konjac powder was higher than that toward LBG or guar gum, which is consistent with other GH family 113 members, such as AaManA (10) and Man113A from Alicyclobacillus sp. strain A4 (19). In contrast, ␤-1,4-mannanases from GH families 5, 26, and 134, such as RmMan5A from Rhizomucor miehei (20), ReTMan26 from ther- mophilic Bacillus subtilis (21), and AoMan134A from Aspergillus oryzae (22), exhibit high hydrolysis preference for LBG.…”
Section: Discussionmentioning
confidence: 99%
“…Mannanases release mainly mannobiose and mannotriose as end products, and exhibit open cleft-shaped active sites able to accommodate up to 5–6 hexose units [ 22 , 23 ]. Based on the amino acid sequences, mannanases have been described in three glycoside hydrolase (GH) families in the Carbohydrate-Active enZYmes database (CAZy) [ 24 , 25 ]: GH5, GH26 and recently also GH113 [ 26 ]. The majority of the characterized mannanases have been classified into the GH5 and GH26 families [ 26 , 27 ], which both belong to the glycoside hydrolase clan GH-A.…”
Section: Introductionmentioning
confidence: 99%
“…최근에는 GH113에 속하는 Alicyclobacillus속 균주의 mannanase [19]와 GH134에 속하는 A. nidulans의 mannanase [13]가 보고되었다. 한편 GH5와 GH113에 속하는 mannanase는 GH26의 mannanase와는 달리 당 전이활성을 보이는 것으로 알려졌다 [11,19].…”
unclassified
“…최근에는 GH113에 속하는 Alicyclobacillus속 균주의 mannanase [19]와 GH134에 속하는 A. nidulans의 mannanase [13]가 보고되었다. 한편 GH5와 GH113에 속하는 mannanase는 GH26의 mannanase와는 달리 당 전이활성을 보이는 것으로 알려졌다 [11,19]. Bacillus속 균주로부터 여러 종류의 mannanases에 대한 반응특성, 구조 및 그 유전자가 밝혀졌으며, 대장균을 비롯하여 B. subtilis, B. brevis [25], Pichia pastoris [8] 등의 다양한 균주를 숙주균으로 하여 Bacillus 유래 의 mannanase를 생산하는 재조합 균주가 개발되었다.…”
unclassified